Discovery of 1a, 2, 5, 5a-tetrahydro-1H-2, 3-diaza-cyclopropa[a]pentalen-4-carboxamides as potent and selective CB2 receptor agonists. Issue 2 (15th January 2015) - Han, Sangdon; Thoresen, Lars; Zhu, Xiuwen; Narayanan, Sanju; Jung, Jae-Kyu; Strah-Pleynet, Sonja; Decaire, Marc; Choi, Karoline; Xiong, Yifeng; Yue, Dawei; Semple, Graeme; Thatte, Jayant; et al.
Graphical abstract